Anti-VEGF drugs compared with laser photocoagulation for the treatment of diabetic retinopathy: a systematic review and economic analysis - Mark Simmonds; Matthew Walton; Rob Hodgson; Alexis Llewellyn; Ruth Walker; Helen Fulbright; Laura Bojke; Lesley Stewart; Sofia Dias; Thomas Rush; John Lawrenson; Tunde Peto; et al. (Health Technology Assessment)
Background Diabetic retinopathy is a major cause of sight loss in people with diabetes, with a high risk of macular oedema, vitreous haemorrhage or other complications. Panretinal photocoagulation is the primary treatment for proliferative retinopathy. Anti-vascular endothelial growth factor drugs are used to treat various eye conditions and may be beneficial for people with proliferative or non-proliferative retinopathy. Methods The Anti-VEGF In Diabetes project sought to investigate the clinical and cost-effectiveness of using anti-vascular endothelial growth factor to prevent retinopathy progression when compared to panretinal photocoagulation or no treatment. A systematic review with network meta-analysis of randomised controlled trials of anti-vascular endothelial growth factor (alone or in combination with panretinal photocoagulation) to treat retinopathy was conducted. The database searches were updated in May 2023. Individual participant data from larger trials were sought. A systematic review of non-randomised studies was performed. Existing cost-effectiveness analyses were reviewed, and a new economic model was developed, informed by the individual participant data meta-analysis. The model also estimated the value of undertaking further research to resolve decision uncertainty. Results The review found that anti-vascular endothelial growth factors produced a slight, and not clinically meaningful, benefit over panretinal photocoagulation in best corrected visual acuity, after 1 year of follow-up in people with proliferative retinopathy (mean difference of 4.5 ETDRS letters; 95% credible interval −0.7 to 8.2). There was no evidence of a difference in effectiveness among the different anti-vascular endothelial growth factors. The benefit of anti-vascular endothelial growth factor appears to decline over time. Anti-vascular endothelial growth factor therapy may be more effective in people with poorer initial visual acuity. Anti-vascular endothelial growth factor had no impact on vision in people with non-proliferative retinopathy. Anti-vascular endothelial growth factor reduces rates of macular oedema and vitreous haemorrhage and may slow down the progression of retinopathy. Anti-vascular endothelial growth factors were predicted to be more costly but similarly effective to panretinal photocoagulation, with a net health benefit of −0.214 quality-adjusted life-years at a £20,000 willingness-to-pay threshold. Only under very select conditions might anti-vascular endothelial growth factors have the potential for cost-effectiveness to treat proliferative retinopathy. There is potentially significant value in reducing uncertainty through further primary research. Conclusions Anti-vascular endothelial growth factor has no clinically meaningful benefit over panretinal photocoagulation for preserving visual acuity, but it may delay or prevent progression to macular oedema and vitreous haemorrhage. The long-term effectiveness and safety of anti-vascular endothelial growth factor treatment are unclear, particularly as additional panretinal photocoagulation and anti-vascular endothelial growth factor treatment will be required over time. Anti-vascular endothelial growth factors are therefore unlikely to be a cost-effective treatment for early proliferative retinopathy compared to panretinal photocoagulation. They are generally associated with higher costs and similar health outcomes across various scenarios. The long-term cost-effectiveness of anti-vascular endothelial growth factor is uncertain due to the lack of long-term clinical evidence. Future work Further, robust studies with more than 2 years follow-up are required to evaluate the long-term efficacy and safety of anti-vascular endothelial growth factor use, and the effect of additional anti-vascular endothelial growth factor and panretinal photocoagulation therapy over time. Clinical trials or observational studies focusing on the use of anti-vascular endothelial growth factor in people with poorer vision at time of treatment may also be useful. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR132948. Plain language summary People with diabetes are at risk of gradually losing their sight because blood vessels in the part of the eye called the retina may become damaged. This condition is called diabetic retinopathy. People with a more severe type of retinopathy called proliferative diabetic retinopathy are usually offered laser treatment. Recently, drugs called anti-vascular endothelial growth factors (anti-VEGFs), which are injected directly into the eye, have been used to treat other eye conditions and might be useful to treat retinopathy. The Anti-VEGF In Diabetes (AVID) project investigated whether anti-vascular endothelial growth factor therapy is clinically useful and cost-effective. We identified and re-analysed all the clinical trials that used one of the three main anti-vascular endothelial growth factor drugs, namely aflibercept, bevacizumab and ranibizumab. We also performed a new economic analysis based on those trials. We found that, after 1 year, people with proliferative diabetic retinopathy who received anti-vascular endothelial growth factor injections saw only a small improvement in vision compared to people who had received laser therapy. People with less severe retinopathy received no benefit to their vision. The benefit of anti-vascular endothelial growth factor injections may also decline over time. However, people who received anti-vascular endothelial growth factor injections were substantially less likely to experience the more severe consequences of vision loss, including where vision is lost in the centre of the eye (called diabetic macular oedema). As most trials ran for < 1 year, the long-term impact of using anti-vascular endothelial growth factor injections repeatedly is still not well understood and requires further clinical research. Anti-vascular endothelial growth factor treatment is more expensive than laser therapy, and because it had only limited benefits for vision, our analyses found that anti-vascular endothelial growth factor injections are not a cost-effective way to treat diabetic retinopathy. This suggests that anti-vascular endothelial growth factor should not be routinely used as a first choice to treat proliferative diabetic retinopathy in people without macular oedema.